The Gravitational Field and the Dark Energy João Carlos Holland de Barcellos - Holland, João Carlos (IJRDO-Journal of Applied Science, 2016)
The dark energy is a “Ad-Hoc” hypothesis postulated with the only purpose of explaining theapparent fast separation of distant galaxies. The effect observed which indicates a rapidseparation is known as “Redshift”. The Redshift of galaxies is currently considered as aDoppler effect of separation.The new theory I will expose explains the Redshift effect with another hypothesis other thanthe rapid separation of galaxies. With this new hypothesis, the existence of dark energy anddark matter is no longer necessary. In case this theory is confirmed, these “dark” entities maybe abandoned permanently.How the idea came to meI was thinking to myself, trying to find a way for the Jocaxian Nothingness (JN) [1] togenerate the Aristotelian logic that could explain the apparent ‘logic’ of our universe. I wasthinking about what kind of thing the JN would be able to generate in the beginning, but thepossibilities were endless… Suppose the JN generates SOMETHING, I thought. This somethingmay or may not have crazy properties, but suppose one of the properties was a restriction tothe generation of things inside or outside its limits… While I was day dreaming, all of theSUDDEN I had the idea that the things that are inside the first generated something coulddecrease in size and the original SOMETHING would remain untouched.If the thing in its interior could decrease in size, the impression given would be that theinitial something would be increasing! An expansion! I therefore abandoned my originalproblem and began to refine this new idea.